2013
DOI: 10.1002/jcp.24472
|View full text |Cite
|
Sign up to set email alerts
|

Retromer Promotes Immune Quiescence by Suppressing Spätzle‐Toll Pathway in Drosophila

Abstract: The Toll and Toll-Like Receptor signaling pathways are evolutionarily conserved pathways that regulate innate immunity in insects and mammals. While efforts have been made to clarify the signal transduction events that occur during infection, much less is known about the components that maintain immune quiescence. Here we show that retromer, an intracellular protein complex known for regulating vesicle trafficking, functions in modulating the Toll pathway in Drosophila melanogaster. In mutant animals lacking r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Inappropriate activation of inflammatory responses or lack of immune signaling lead to serious conditions such as inflammatory diseases or immunodeficiency, respectively. Recent studies reveal that innate immunity is regulated by multiple factors, including sumoylation and the retromer complex, which fine tune immune activity (32,33). The present study clearly showed that glycosylation plays an important role in maintaining innate immune homeostasis and activation of immune responses.…”
Section: Discussionsupporting
confidence: 63%
“…Inappropriate activation of inflammatory responses or lack of immune signaling lead to serious conditions such as inflammatory diseases or immunodeficiency, respectively. Recent studies reveal that innate immunity is regulated by multiple factors, including sumoylation and the retromer complex, which fine tune immune activity (32,33). The present study clearly showed that glycosylation plays an important role in maintaining innate immune homeostasis and activation of immune responses.…”
Section: Discussionsupporting
confidence: 63%
“…dOCRL-TagRFPT localized to discrete puncta at the hemocyte plasma membrane and throughout the cytoplasm ( Fig 3A ). These puncta colocalized most strongly with He-Gal4-driven GFP tagged clathrin light chain (Clc), and moderately colocalized with other compartment markers ( Fig 3B , S4A Fig ), including endogenously tagged YFP-Rab5 (early endosomes), YFP-Rab7 (late endosomes), YFP-Rab11 (recycling endosomes), and He-GAL4-driven Vps35-GFP (a component of the endosomal cargo-sorting retromer complex, which has itself previously been implicated in restricting innate immune activation [ 18 , 22 ]). Interestingly, dOCRL exhibited a qualitatively different pattern of association with different compartments.…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila , the innate immune system is poised to respond quickly and effectively to infection. Mutants in a variety of components of the endosomal trafficking system exhibit various features of immune activation, including increased hemocyte abundance [ 18 22 ], but it has remained unclear which specific immune tissues or pathways are altered or how this leads to hemocyte activation. Here we show that dOCRL controls endosomal traffic in Drosophila larval hemocytes to autonomously restrict immune cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, distinct SNX-BAR proteins control a currently not well-defined Retro-2-sensitive retrograde trafficking pathway that delivers distinct nutrients to the bacteria or alternatively could be related to factors controlling innate immunity. The idea of an innate immunity-related function of the retromer is further supported by the recently published observation in Drosophila that retromer can also control the Toll pathway [ 51 ].…”
Section: Discussionmentioning
confidence: 99%